Cabbage‐centre grub (Hellula hydralis Guenée) (Lepidoptera: Pyralidae): a new pest challenge to long‐season canola grown for forage and grain in southern Australia. Issue 2 (9th March 2022) - Nash, Michael
Abstract: Canola crops grown across southern Australia are subject to damage from more than 40 invertebrate species. Shifts within this invertebrate pest complex have evolved due to changing management practices. The latest change is the sowing of winter canola cultivars in the proceeding spring (September–November), grazing during late summer to early winter (February–June) and then 'locking up' for grain harvest in December/January. Complementary to this practice is the sowing of longer‐season spring cultivars in early autumn, also for grazing. Do long‐growing‐season crops create green bridges for insects and diseases? In the autumn of 2016, significant damage to forage canola caused by Hellula hydralis Guenée, 1854 was reported. The widespread occurrence of H. hydralis moths across south‐east Australia is expected due to it migrating on southerly airflows from where it is a pest in subtropical vegetable crops. Previously, H. hydralis had been considered as an occasional pest in forage turnips grown over the summer–autumn period. However, the occurrence of multiple larval instars in winter canola for a prolonged period in late summer and early autumn of 2016 across the high‐rainfall zones of south‐east Australia causing substantial loss of dry matter has not been reported previously. Little is known about this native species, but international literature exists for related pest species. The likely factors and implications of the unusually high occurrence of H. hydralis in forage canola are discussed. Pest report data indicate that H. hydralis continues to cause damage, suggesting that the growing of long‐season forage canola is providing another, more suitable, over‐summer breeding ground in southern Australia for this native species. Long‐term research on crop and non‐crop hosts is necessary to understand, hence manage, H. hydralis as a pest of canola.